Open Space Worship: A Religious Identity of the Johane Masowe Chishanu Church in Zimbabwe - Phillip Musoni; Paul H. Gundani (Journal for the Study of Religion)
This study examines ‘open space’ worship that has typified the religious identity of the Johane Masowe Chishanu Church (‘John of the wilderness’ Churchthat congregates on Fridays) in Zimbabwe. The Johane Masowe Chishanu Church (JMCC) is a Zimbabwean African indigenous church with branches in many countries. These congregations, being in Zimbabwe and other countries,are recognizable by their white garments and gatherings in open spaces for church services.The practice of congregating in open spaces has been condemned by city fathers, town planners,and government autho-rities guided by health policies and by-laws (Lubinda 2015; Ncube 2016). In spite of these condemnations, the JMCC has continued to use available open spaces for its services. Our understanding is that congregating in open spaces has become an integral part of the JMCC’s history and theological identity. In this article, we examine the veracity and provenance of this assumed identity by interrogating the church’s traditions, its relations with colonial authorities, and its theology of open spaces. Borrowing from the theory on identity formation (Dominelli 2002), our contention is that a combination of factors contributes to the JMCC’s continued practice of gathering for worship inopen spaces. These factors include the sectarian influences on the JMCC, the African spiritual ethos within which it was founded, as well as the colonial ‘othering’ and subsequent marginalization.